Manajemen Pengendalian Penyakit ISPA di Puskesmas Bunut Kabupaten Pelalawan Tahun 2025 - Sandra Marika; Zainal Abidin; Toni Toni (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Acute Respiratory Infection (ARI) remains a major public health problem in Indonesia, including Pelalawan Regency. Community Health Centers play a strategic role in ARI control through promotive and preventive approaches. This study aims to analyze the management of ARI control at Bunut Public Health Center, Pelalawan Regency in 2025. A descriptive qualitative method with a residency-based approach was used through observation, in-depth interviews, and document review. The analysis focused on management functions including planning, organizing, directing, and controlling. The results indicate that ARI control planning has referred to national policies; however, limitations in human resources and weak program evaluation were identified. Organizational aspects showed multiple job assignments among health promotion staff. Direction and control functions were implemented but not yet optimal in reducing ARI incidence. Strengthening health promotion management, improving human resource capacity, and conducting continuous evaluations are necessary to enhance ARI control effectiveness.